Search for the lepton-flavor violating decay 𝐵0𝑠 →𝜙⁢𝜇±⁢𝜏∓ - Aaij, Roel; Bachmann, Sebastian; Carus, Leon; Caspary, Rowina; Celani, Sara; Cocha Toapaxi, Carlos; De Cian, Michel; Dittmann, Lucas; Glaser, Fabian; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; Herrero Gascón, Paula; et al. (Physical review, 2024)
A search for the lepton-flavor violating decays 𝐵0𝑠 →𝜙⁢𝜇±⁢𝜏∓ is presented, using a sample of proton-proton collisions at center-of-mass energies of 7, 8, and 13 TeV, collected with the LHCb detector and corresponding to a total integrated luminosity of 9 fb−1. The 𝜏 leptons are selected using decays with three charged pions. No significant excess is observed, and an upper limit on the branching fraction is determined to be ℬ⁡(𝐵0𝑠→𝜙⁢𝜇±⁢𝜏∓) <1.0 ×10−5 at 90% confidence level.
Im Titel ist 0 hochgestellt, s tiefgestellt, dabei steht 0 über s; die Zeichen ± und ∓ sind ebenfalls hochgestellt
LHCb Collaboration: R. Aaij, S. Bachmann, L. Carus, R. Caspary, S. Celani, C. Cocha Toapaxi, M. De Cian, L. Dittmann, F.C. Glaser, X. Han, S. Hansmann-Menzemer, P. Herrero Gascon, C. Langenbruch, B. Leverington, J. Marks, M.P. Morgenthaler, M. Ruiz Diaz, G. Tuci, L.H. Uecker, D.J. Unverzagt, U. Uwer, C. Wang, L. Witola, Y. Zhao, A. Zhelezov [und zahlreiche weitere]
Gesehen am 14.01.2026